Masalah Penyesuaian Semasa Transisi Persekolahan Pelajar Tingkatan Satu Sekolah Menengah Agama Kedah - Ahmad Rushidi, Ramli (1999)
This research was intended to investigate and identify factors effecting adjustment problems among form one students in religious schools in the state of Kedah during school transitions from primary to secondary schools. Four religious schools were chosen for this research with a total of 547 respondents were involved consisting of form one students ranging in the age of 13 years old. The independent variables were factors such as the demographic, financial, academics, food and lodging, social and orientation program. Demographic factors consisted of gender, status in the family, monthly financial income of the family and the number of siblings in other school’s hostels. Likewise, the dependent variables were the overall adjustment problems. Findings suggested that generally, the students did not manifest any sign of adjustment problems during school transitions. However, students were found to have financial and academic problems with orientation program having the least problems. Results also indicated that there were no marked differences between demographic factors and adjustment problems. Additionally, results also indicated that very significant relationships existed between factors of academic, food and lodging, social, orientation program and adjustment problems. Finally, factors of food and lodging were found to have exerted most influence on adjustment problems, followed by orientation programs and social factors. Recommendations were made to assist the relevant authorities mitigate the adjustment problems faced by the students and recommendations for further research were also put forward.